Sustainable Inland Waterway Transportation Systems: Framework Proposal - Pratas, João; Garrido, Susana; Pimentel, Carina (European Journal of Sustainable Development, 2023)
Large cities are widely recognized as major contributors to climate change due to their high energy demand and heavy reliance on on-road transportation. Urban mobility today brings additional concerns about predicted demands arising from people's necessities of living in cities and their respective needs to travel in different forms, either for personal or professional purposes. This study based on a literature review and case studies analysis proposes a framework to support the implementation of Sustainable Inland Waterway Transportation Systems as an alternative to road transport. The proposed framework is tested in São Paulo City (Brazil). In the implementation of a sustainable inland waterway transportation system, the following factors were identified as strategic: user characteristics and behaviour, operators’ characteristics and behaviour, investment in infrastructures, regulation and taxation, and Government. Infrastructure and strategic planning are areas that deserve further investigation. Research could focus on developing strategies for efficient routing, taking into account various potential limitations, water navigability, vessel capacity, traffic management, and transshipment locations. Intermodality between different transport modes is a crucial area that needs to be addressed to ensure full integration into the multimodal network. Investigating connectivity and information sharing systems between modes would enhance the overall efficiency and attractiveness of waterway transportation in the city's ecosystem. Keywords: transportation, waterway, framework, sustainability, case studies.